KAJIAN BAHAN HUMAT UNTUK MENINGKATKAN EFISIENSI PEMUPUKAN NPK PADA BIBIT KELAPA SAWIT DI TANAH SULFAT MASAM - Supriyo, A Supriyo, A; R.Dirgahayuningsih R.Dirgahayuningsih; S.Minarsih S.Minarsih (Universitas Muhammadiyah Purwokerto, 2013)
The opportunity of agribusiness palm oil plantation related to the increased of plam oil demand in the world. The business of palm oil plantation in Indonesia now is facing the limited land resources. Development of palm oil plantation to sub optimals lands such as acid sulphate soils were estimated in 2.0 millions hectares in Indonesia. The palm oil cultures in acid sulphate soils need the appropriate of inputs and efficiency based in land characteristics. Glass house experiments was conducted with randomized complete designs with three replications. An experiments consisted of two sub aactivities i.e combination of NPK dosage with humic matterial application methods. Each treatment consisted 30 plant/polybag so that totals 720 plants/polybag, Sub activity 1 (Humic matterial coated on NPK fertilizers) : a) 100 % NPK + no humic coating 0 % , b) 100 % NPK + humic coated 0,5 %, c) 75 % NPK + humic coated 1,0 %, d) 50% NPK + humic coated 2%. Humic applicated in % (v/w). Sub activities 2 (application of humic liquid was sprayed). : were kind of four of treatments (1) 100 % NPK 100 % with out humic, (2) 100 % NPK + humic (liquid) 3 cc/plant, (3) 75 % NPK + Humic (liquid) 3 cc/plant, and (4) 50% NPK + humic (liquid) 6 cc/plant.. Application of humic was sprayed suited in on each treatments 20 times equivalent 1 – 2 liters, humic acid was diluted in 20 l water was applicatid in polybags eachs 3 – 4 weeks. Parameter were observed in soil chemical characteristics before planting, plants growth (plant height, plant diameters and leaf numbers per plant) and leaf macronutrient contents such as N, P, K, Ca and Mg. Data were collected by using variant analized. Differents of the treatments were tested by DMRT0.05. Result showed that (1) Fertilizer appplied 75% NPK recommended + liquid humic 1% (v/w) (coated) better than to increase of plant height, plant diameters and leaf numbers of palm oil at 6 and 7 month ago compared to others.(2) Applicaton of 75% NPK with sprayed 3 cc humic per plant will increased the plant height most, plant diameters and leaf numbers at age of 6 and 7 month ago than the others. (3) Applivcation of humic matter 1% (v/w) (coated) at 75 % NPK better than application of 75 % NPK applied + humic (liquid) 3 cc per plant that was sprayed in the soil polybag on plant height, diameter plant and number of leaf per plant and to increase of N, P and K content of the plant. Key words : Humic matter, fertilizer, palm oil, acid sulphate soils.